The Paradigmatic Model of Virtual Education in the Islamic Azad Universities of Sistan and Baluchestan: Identification of Key Factors and Optimization Strategies - Naseripour, Aqil; Kordestani, Fereshteh; Shariatmadari, Mehdi; Hamidifar, Fatemeh (International Journal of Education and Cognitive Sciences, 2024)
Purpose: The aim of this research is to present a paradigmatic model for virtual education in the Islamic Azad Universities of Sistan and Baluchestan province. Methods and Materials: Considering the nature of the subject and the objectives, this study adopts an interpretive paradigm with a qualitative approach. The research method is grounded theory, and the study population consists of experts and specialists in the fields of educational management and virtual education. Purposeful qualitative sampling and criterion-based and snowball selection techniques were employed, resulting in a sample size of 20 participants. Semi-structured interviews were used as the research instrument. Data analysis was conducted using MAXQDA software. This study identified six categories, 25 concepts, and 142 codes, which were organized into a paradigmatic model. Findings: The findings revealed that due to factors such as innovation, creativity, ease of access, promotion of educational equity, foresight, and achieving competitive advantage (causal factors), virtual education should focus on dimensions such as the application of various virtual education methods, the characteristics of teaching methods, and the evaluation of education (central phenomenon). These should be addressed through strategies such as enhancing purposeful educational quality, improving communication and interaction between instructors and students, fostering a culture of online trust, and improving technical infrastructure. The characteristics of instructors, students, and educational content (contextual factors), alongside family, psychological-personal, cultural-social, financial and legal, management, educational, and infrastructural challenges (intervening factors), influence virtual education, leading to both positive and negative outcomes. Conclusion: This study highlights the complexities of virtual education, emphasizing the need for innovative strategies, improved infrastructure, and continuous evaluation to enhance its quality, accessibility, and alignment with educational goals.